Organic chemistry - Klein, David (Hoboken, John Wiley, 2015)
In Organic Chemistry, 2nd Edition, Dr. David Klein builds on his unique skills-based approach, including all of the concepts typically covered in an organic chemistry textbook, but placing special emphasis on skills development to support these concepts. This emphasis upon skills development provides two-semester Organic Chemistry students with a greater opportunity to develop proficiency in the key skills necessary to succeed in organic chemistry.
Glossary 1-12p.; Index 1-21p.
Keywords: Alkynes; Amines; Aromatic compounds; Synthesis; Acids and bases